Diagnostic Imaging Methods and Comparative Analysis of Orbital Cavernous Hemangioma - Zhang, Li; Li, Xuying; Tang, Fei; Gan, Lu; Wei, Xin (Frontiers in Oncology, 2020)
Orbital cavernous hemangioma is the most common primary tumor in the orbit. With the development of histopathology, it has been confirmed that cavernous hemangioma is not a real tumor, but a special type of vascular malformation. Cavernous hemangioma malformation(CVM) is a more appropriate way to name it. At present, surgical resection is the main treatment for CVMs. The prognosis of the surgery mainly depends on the location and the size of the lesion as well as its relationship with the optic nerve. Therefore, effective imaging information is of great importance. This paper analyzes the radiological imaging characteristics and the advantages and disadvantages between them, including ultrasound, CT, MRI, and SPECT/CT imaging of CVMs, hoping to help improve our understanding of CVMs.